CRISPR/Cas9-mediated precise genome modification by a long ssDNA template in zebrafish - Bai, Haipeng (BMC Genomics, 2020)
BACKGROUND: Gene targeting by homology-directed repair (HDR) can precisely edit the genome and is a versatile tool for biomedical research. However, the efficiency of HDR-based modification is still low in many model organisms including zebrafish. Recently, long single-stranded DNA (lssDNA) molecules have been developed as efficient alternative donor templates to mediate HDR for the generation of conditional mouse alleles. Here we report a method, zLOST (zebrafish long single-stranded DNA template), which utilises HDR with a long single-stranded DNA template to produce more efficient and precise mutations in zebrafish. RESULTS: The efficiency of knock-ins was assessed by phenotypic rescue at the tyrosinase (tyr) locus and confirmed by sequencing. zLOST was found to be a successful optimised rescue strategy: using zLOST containing a tyr repair site, we restored pigmentation in at least one melanocyte in close to 98% of albino tyr(25del/25del) embryos, although more than half of the larvae had only a small number of pigmented cells. Sequence analysis showed that there was precise HDR dependent repair of the tyr locus in these rescued pigmented embryos. Furthermore, quantification of zLOST knock-in efficiency at the rps14, nop56 and th loci by next generation sequencing demonstrated that zLOST showed a clear improvement. We utilised the HDR efficiency of zLOST to precisely model specific human disease mutations in zebrafish with ease. Finally, we determined that this method can achieve a germline transmission rate of up to 31.8%. CONCLUSIONS: In summary, these results show that zLOST is a useful method of zebrafish genome editing, particularly for generating desired mutations by targeted DNA knock-in through HDR.